Analysis and design of a double-sided rotor iron-cored radial flux permanent magnet synchronous wind turbine generator - Van Wijk, Johannes Hendrik (Stellenbosch : Stellenbosch University, 2012)
Thesis (MScEng)--Stellenbosch University, 2012.